GAMBARAN PENGETAHUAN, SIKAP, DAN TINDAKAN PETANI PENYEMPROT PADA PENGGUNAAN PESTISIDA DI DESA SUGIHEN KECAMATAN DOLAT RAYAT TAHUN 2013 - Florentina Flisia Brahmana; Lina Tarigan; Umi Salmah (Lingkungan dan Kesehatan Kerja, 2014)
Pesticide is chemical compound , which is used to eradicate plant’s pest. The use of pesticides that are not as recommended may cause negative impact on health. Karo Regency is one of agricultural centre where the farmers used pesticides This study was a descriptive research which is aimed to find the description of farmers knowledge, attitude, and practice in the use of pesticides in Sugihen Viilage, Dolat Rayat Sub District, Karo Regency in 2013. Result showed respondent’s knowledge : pesticides must be used according to the target (100%), insecticide is different with fungicide (86,7%), the right storage of pesticides (96,75%), pesticide must be mixed in outdoor (60%), the right time of spraying pesticide (100%), the use of APD (100%), dose of pesticide (96,7%), how to manage pesticides container (43,3%), pesticide gave negative effect to human health (100%). Respondent’s attitude : pesticides must be registered (63,3%), pesticides must be stored in their original containers (90%), using a tool to mix the pesticide (100%), follow the wind direction when spraying pesticide (93,3%), using APD is important (100%), eating, drinking, and smoking aren’t allowed when spraying pesticide (96,7%), the waste of mixed pesticide must be disposed (90%), farmers should take a bath after spraying pesticides (100%). Respondent’s practice : Buying pesticides in a legal shop (100%), keeping the pesticide in a werehouse (90%), time interval for spraying aren’t being adjusted, kept spraying pesticide though there is a high wind (96,7%), spraying pesticide without considering wind ward (86,7%), the use of hat and overalls clothes (96,7%), the most activity after spraying pesticides are washing their hand (86,7%) and smoking (80%), the waste of pesticide’s container is sold to shelter secondhand goods (66,7%). Generally, there were many poorly action of using pesticide by farmers so it is important to give them counseling and checking the level of enzyme cholinesterase regularly.